Photoresponse of supramolecular self-assembled networks on graphene–diamond interfaces - Wieghold, Sarah (Nat Commun, 2016)
Nature employs self-assembly to fabricate the most complex molecularly precise machinery known to man. Heteromolecular, two-dimensional self-assembled networks provide a route to spatially organize different building blocks relative to each other, enabling synthetic molecularly precise fabrication. Here we demonstrate optoelectronic function in a near-to-monolayer molecular architecture approaching atomically defined spatial disposition of all components. The active layer consists of a self-assembled terrylene-based dye, forming a bicomponent supramolecular network with melamine. The assembly at the graphene-diamond interface shows an absorption maximum at 740 nm whereby the photoresponse can be measured with a gallium counter electrode. We find photocurrents of 0.5 nA and open-circuit voltages of 270 mV employing 19 mW cm(−2) irradiation intensities at 710 nm. With an ex situ calculated contact area of 9.9 × 10(2) μm(2), an incident photon to current efficiency of 0.6% at 710 nm is estimated, opening up intriguing possibilities in bottom-up optoelectronic device fabrication with molecular resolution.